1989
DOI: 10.1001/jama.1989.03420130045021
|View full text |Cite
|
Sign up to set email alerts
|

Personal Watercraft Injuries

Abstract: of legionellae are substantially more resistant to chlorine than a number of other waterborne bacteria.2 Furthermore, legionellae obtained from a hyperchlorinated hospital plumbing system seemed to be even more resistant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Unfortunately, there is a paucity of literature reporting the serious outcomes of common PWC accidents. Vernberg et al [2] published the first report of injuries related to PWC in 1989; more than a decade after these vehicles became available. They described an incident involving six PWC riders and six swimmers, of which ten were hospitalized and two died due to head trauma.…”
Section: Common Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is a paucity of literature reporting the serious outcomes of common PWC accidents. Vernberg et al [2] published the first report of injuries related to PWC in 1989; more than a decade after these vehicles became available. They described an incident involving six PWC riders and six swimmers, of which ten were hospitalized and two died due to head trauma.…”
Section: Common Injuriesmentioning
confidence: 99%
“…Safety recommendations have been proposed as early as 1989 in the scientific literature. Vernberg et al [2] recommended that: (1) PWCs should be used in an area separate from swimmers; (2) should require riders to be a minimum age; (3) a life jacket should be mandatory; (4) and protective headgear should be required. Unfortunately, these simple safety recommendations still go unheeded by many PWC users two-decades later.…”
Section: Safetymentioning
confidence: 99%
“…The magnitude of this public health problem, and research to prevent PWC related injuries, has not been adequately addressed. [3][4][5][6] This may be due to the relatively recent emergence of the PWC as a popular watercraft or to the lack of detailed information or surveillance of incidents involving PWCs.…”
Section: (5) Lessons Learnedmentioning
confidence: 99%
“…The magnitude of this public health problem, and research to prevent PWC related injuries, has not been adequately addressed. [3][4][5][6] This may be due to the relatively recent emergence of the PWC as a popular watercraft or to the lack of detailed information or surveillance of incidents involving PWCs. This paper describes childhood use and injury risk associated with PWCs in Arkansas, the availability and accuracy of injury data, and suggests areas for improved surveillance and countermeasures.…”
Section: (5) Lessons Learnedmentioning
confidence: 99%
“…3 It has also been suggested that a comprehensive approach that focuses on adolescent risk taking behaviour in general may provide a more eVective injury prevention strategy than approaches targeted on specific injury problems. 4 Providing local data to a community to increase their awareness of the need to develop strategies to prevent injury has been previously demonstrated. 5 Very few, however, have focused exclusively on adolescents.…”
mentioning
confidence: 99%